2014
DOI: 10.1016/j.nicl.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of the N400 in single subjects: Implications for patients with disorders of consciousness

Abstract: Functional neuroimaging assessments of residual cognitive capacities, including those that support language, can improve diagnostic and prognostic accuracy in patients with disorders of consciousness. Due to the portability and relative inexpensiveness of electroencephalography, the N400 event-related potential component has been proposed as a clinically valid means to identify preserved linguistic function in non-communicative patients. Across three experiments, we show that changes in both stimuli and task d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 52 publications
3
72
0
Order By: Relevance
“…We used the inexact augmented Lagrange multiplier method for computing rPCA37 and applied the method on the combined set of subjects.”16 This was done because the rPCA method allows for the substitution of outlier samples with interpolated data, ensuring the temporal continuity of the signal, which is essential to our analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the inexact augmented Lagrange multiplier method for computing rPCA37 and applied the method on the combined set of subjects.”16 This was done because the rPCA method allows for the substitution of outlier samples with interpolated data, ensuring the temporal continuity of the signal, which is essential to our analysis.…”
Section: Methodsmentioning
confidence: 99%
“…While such EEG measures appear to index cognitive processes, it is not clear that ERPs capture the type of auditory attention required to comprehend speech in everyday environments. Importantly, previous attempts to probe semantic verbal processing in DOC patients using EEG with short speech segments (mostly the N400 ERP component)14, 15 have generally failed to make diagnostic predictions for individual patients 16. In contrast, EEG responses to longer speech segments have shown promise in quantifying consciousness in acute traumatic brain injury 17…”
Section: Introductionmentioning
confidence: 99%
“…In order to boost the N400 and LPC, we could use active tasks focused on semantic attributes of word pairs, rather than instructing subjects to simply attend to the stimuli without engaging in any specific task. Indeed, (Cruse et al, 2014) designed three experiments in normal controls, and showed that while N400 could be detected at the single-subject level in a semantically related word-pair paradigm using an active response task in 75% (9/12) of subjects, this proportion dropped to 58% (7/12) when subjects were instructed to simply pay attention to the semantic relation covertly, and to 0% when they were asked to passively listen to the material. Then in a second experiment, they showed that the use of word-pair stimuli generated from normative associations -as done in our work -increased the detection of N400 in the passive condition in 50% of subjects.…”
Section: Verbal Semantic Processing In Conscious Healthy Subjectsmentioning
confidence: 99%
“…Data from the mental imagery paradigm were preprocessed using SPM8 (http://www.fil. 42,44 In the first step, data were compared at each time point using a t test. 13 For the selective attention paradigm, preprocessing was performed with AA software.…”
Section: Fmri Data Acquisition and Preprocessingmentioning
confidence: 99%
“…43 This technique has been described in detail previously. 42,44 In the first step, data were compared at each time point using a t test. In the second step, t values of adjacent spatiotemporal points with p < 0.05 were clustered together by summating their t values.…”
Section: Eeg Data Acquisition and Preprocessingmentioning
confidence: 99%